Sex Differences in Cardiovascular Aging and Heart Failure - Oneglia, Andrew (Curr Heart Fail Rep, 2020)
PURPOSE OF THE REVIEW: This review summarizes sex-related changes in the heart and vasculature that occur with aging, both in the presence and absence of cardiovascular disease (CVD). RECENT FINDINGS: In the presence of CVD risk factors and/or overt CVD, sex-specific changes in the number of cardiomyocytes, extent of the myocardial extracellular matrix, and myocellular hypertrophy promote unique patterns of LV remodeling in men and women. In addition, age- and sex-specific vascular stiffening is also well established, driven by changes in endothelial dysfunction, elastin–collagen content, microvascular dysfunction, and neurohormonal signaling. Together, these changes in LV chamber geometry and morphology, coupled with heightened vascular stiffness, appear to drive both age-related increases in systolic function and declines in diastolic function, particularly in postmenopausal women. Accordingly, estrogen has been implicated as a key mediator, given its direct vasodilating properties, association with nitric oxide excretion, and involvement in myocellular Ca(2+) handling, mitochondrial energy production, and oxidative stress. SUMMARY: The culmination of the abovementioned sex-specific cardiac and vascular changes across the lifespan provides important insight into heart failure development, particularly of the preserved ejection fraction variety, while offering promise for future preventive strategies and therapeutic approaches.